In vitro α-amylase inhibitory effect of TLC isolates of Aloe megalacantha baker and Aloe monticola Reynolds - Gebretsadkan Hintsa Tekulu; Ephrem Mebrahtu Araya; Hayelom Gebrekirstos Mengesha (BMC, 2019)
Abstract Background About 425 million adults had diabetes mellitus globally in 2017. Type 2 diabetes accounts for the enormous majority of diabetes cases and it is gradually growing which is predicted to increase by 48% in 2045. Imbalanced cellular carbohydrate and lipid metabolism cause an increase in postprandial blood glucose level which eventually leads to the onset and progression of type 2 diabetes mellitus. The lack of effective and safe carbohydrate hydrolyzing enzyme inhibitors contributes to the increasing prevalence. Thus, this study was targeted to assess the α-amylase inhibitory potential of isolates obtained from Aloe megalacantha Baker and Aloe monticola Reynolds, which are among the commonly used folkloric remedies for the management of diabetes mellitus. Method The α-amylase inhibitory effect of Aloe megalacantha Baker and Aloe monticola Reynolds were evaluated using the 3,5-dinitro salicylic acid method. 2, 2-Diphenyl-2-picrylhydrazyl free radical scavenging property was also used to test the antioxidant effect of both plants. Results were analysed using GraphPad Prism software version 8. Results The more polar isolates (AM1 and AG1) were possessed stronger α-amylase inhibition activity than the leaves latex and the other strains (AM2 and AG2). Leaf latex of A. megalacantha, AM1, AM2 , leaf latex of A. monticola, AG1, and AG2 were found to have an IC50 value of 74.76 ± 1.98, 37.83 ± 3.31, 96.75 ± 1.98, 78.10 ± 1.88, 56.95 ± 1.88 and 64.03 ± 3.60 μg/mL, respectively (P < 0.001). The leaf latexes of A. megalacantha and A. monticola showed a significant (P < 0.001) free radical hunting property with an IC50 value of 890.1 ± 1.73 and 597.5 ± 2.02 μg/mL, respectively. Conclusion Hence, the outcomes of the present investigation partly justify the acclaimed use of Aloe megalacantha and Aloe monticola for the treatment of diabetes.